2019
DOI: 10.1186/s11658-018-0134-9
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing microRNA-29c promotes biliary atresia-related fibrosis by targeting DNMT3A and DNMT3B

Abstract: This study was designed to investigate the potential role of microRNA-29c (miR-29c) in biliary atresia-related fibrosis. The expression of miR-29c was determined in 15 pairs of peripheral blood samples from infants with biliary atresia (BA) and infants with non-BA neonatal cholestasis using quantitative real-time PCR. EMT was established by induction with TGF-β1 in HIBEpiC cells. MiR-29c was inhibited by lipofectamine transfection. The expressions of proteins related to epithelial–mesenchymal transition (EMT),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The Hippo signaling pathway inhibits cell growth [29]. In mammals, upstream membrane protein receptors of the Hippo signaling pathway receive extracellular growth-inhibitory signals [30]. Once the extracellular growth-inhibitory signals are sensed, they activate a series of kinase cascade phosphorylation reactions and eventually phosphorylate downstream effector YAP and TAZ [31].…”
Section: Discussionmentioning
confidence: 99%
“…The Hippo signaling pathway inhibits cell growth [29]. In mammals, upstream membrane protein receptors of the Hippo signaling pathway receive extracellular growth-inhibitory signals [30]. Once the extracellular growth-inhibitory signals are sensed, they activate a series of kinase cascade phosphorylation reactions and eventually phosphorylate downstream effector YAP and TAZ [31].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al . [ 43 ], Szabo and Bala [ 44 ] and Kriegel et al . [ 45 ] showed that low levels of mir-29 are associated with an increase in fibrosis in BA patients.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of mir-29 have been shown to have anti-fibrotic effects by suppressing collagen 1 A1 mRNA and its protein expression, reducing HSC activation [42]. Wang et al [43], Szabo and Bala [44] and Kriegel et al [45] showed that low levels of mir-29 are associated with an increase in fibrosis in BA patients. Our results showed that miR-29b-3p was expressed at low levels in all samples, except sample 6 (BASM), where no expression was found.…”
Section: The Mir-29 Familymentioning
confidence: 99%
“…The inflammatory fibrosis process in bile ducts is regulated by several pathways, such as the Notch and transforming growth factor-β/Smad signaling pathways ( 7 ). Recent studies have shown that the Sonic hedgehog (Shh) signaling pathway and epithelial–mesenchymal transition (EMT) may also play an important role in this process ( 8 , 9 ). The Shh signaling pathway is involved in embryonic development, and several studies have suggested that the GLI family, the crucial factors of the Shh pathway, is highly expressed in the BA process ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%